Smells like money: Mexican employee endurance in a southwest Kansas meatpacking plant - Ruiz Ruiz, Zaira Nohely (Kansas State University, 2019)
It is no secret to say working in a meatpacking plant can be very difficult. In the words of one employee, “it is not an animal slaughterhouse, but a human one”. National Beef Packing (NBP) opened a branch in Liberal, Kansas in the 1980s. Since then, the plant has recruited immigrant labor from all over the world. Presently in 2019, Mexican immigrants and their U.S. born children and grandchildren—who primarily identify as Mexican—make up the majority of employees at NBP. Many U.S. born self-identifying Mexican employees have parents and grandparents who work, or have worked, at the plant. All three generations claim conditions are terrible and advise people not to work there. Yet, they persist. How do Mexican employees endure work in the plant over time, across generations, and while employees from other parts of the world come and go? To answer my question, I conducted in-depth interviews with 23 of first through third-generation Mexican immigrant employees. I analyzed patterns and variations in their strategies for enduring difficult working conditions, including inter-ethnic competition or solidarity, over time. I found that Liberal’s status as a rural, ethnic enclave provides Mexican employees with a sense of certainty that makes enduring the plant conditions possible, and sometimes desirable. Liberal serves as an ethnic enclave that provides social and economic networks and motivate ethnic retention, sometimes protecting employees from insecurity and discrimination, and sometimes limiting their willingness to seek opportunities beyond Liberal and the plant. I claim endurance strategies are aimed at sustaining membership in this Mexican ethnic enclave, in order to increase the likelihood of higher social mobility for oneself and family. In the process, people—sometimes multiple generations of local families, must tolerate some of the most intolerable working conditions in the country.
Keywords: Mexican immigrant; Meatpacking; Liberal, Kansas; Rural ethnic enclave; National Beef Packing